Calculation of Financial Ratios on PT ACE Hardware Indonesia Tbk - Jessica Gabrella Kuhon; Nanik Lestari (Journal of Applied Accounting and Taxation, 2016)
The purpose of this research was to find out how the development ratio of liquidity, solvency and profitability at PT ACE Hardware Indonesia Tbk. Data used are descriptive data in the form of financial statements, financial position report, income statement, and cash flow statement PT ACE Hardware Indonesia Tbk 2009-2014 period obtained from Indonesia stock exchange official website "http://www.idx.co.id". The research results showed that the ratio of liquidity at PT ACE Hardware Indonesia Tbk very good in guarantee obligations as seen from the current ratio of 181%, 781, 508%, 585%, 400%, and 508%, whereas the quick ratio of 659%, 382%, 157%, 144%, 42% and 96%. Inventory turnover ratio amounted to 6.98 8.08 times, times, 2.93 times, 3.67 times, 1.62 times and 1.94 times. If seen from the solvency ratio of the growth and financial performance are still in good condition as seen from debt to total asset ratio of 10%, 20%, 15%, 15%, 10% and 19%. The times interest earned ratio of 96435.16 times, 12 times, 12 times, 235.26 times, 181.48 176.92 times and times. The performance and development of the company can also be seen from the side i.e. profitability ratio profit margin on sales amounted to 11%, 20%, 11%, 13%, 12% and 12% and the rate of return on assets amounted to 14%, 16%, 20%, 25%, 18% and 20%.